Proportionality in international humanitarian law : refocusing the balance in practice / Jeroen van den Boogaard. - Boogaard, Jeroen van den (Cambridge University Press, 2023)
This book seeks to clarify the legal concept of proportionality in international humanitarian law, as it applies during armed conflict. It is argued in the book that a refocus of the interpretation of the proportionality rule is warranted to enhance the protection of civilians. More precisely, this book seeks to dissect the origins of the rule, determine how its components must be interpreted and how it is to be applied in practice. The book considers practical situations that may arise in the conduct of military operations and searches for the limits international humanitarian law sets to commanders' assessments of proportionality during armed conflict. The book concludes that proportionality is an inherently subjective and imprecise yardstick that nonetheless serves to protect civilians during armed conflict.